A Case Study Of Axis REITs Managers Berhad - Haw, Ng Keat (2009)
This case study aims to investigate Axis REITs Managers Berhad as well as to examine the overall performance of Axis REITs within the Malaysia REITs market. Besides, this case study also compares Axis REITs performance with other Malaysia REITs.